2019
DOI: 10.1021/acsbiomaterials.9b00526
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Infrared Luminescence and Photothermal Properties of Double-Shelled Rare-Earth-Doped Nanoparticles for Biomedical Applications

Abstract: The nascent field of theranostics, which couples targeted therapy with diagnostics, has catalyzed efforts toward improved nanoprobe designs that facilitate both localized treatment and diagnostic imaging. Rare-earthdoped nanoparticles (RENPs) have emerged as a leading candidate for theranostics because of their versatile synthesis and modification chemistries, photostability, and relative safety. Furthermore, their bright, tunable fluorescence using near-infrared (NIR) excitation enables multispectral imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…The rapid in vivo clearance was most likely facilitated by the degradation of SrFCl:Nd 2 in the aqueous environment. Compared to our previous studies where particle clearance from the tumor site was typically observed between 2 to 3 days using much smaller uoride nanocrystals, 5,6,19 the much faster clearance of the much larger SrFCl:Nd 2 @PDA within 12 h post injection suggests that the solubilization of SrFCl was instrumental towards the rapid inorganic nanocrystal clearance. The strong PA signal aer intravenous injection coupled with complete clearance at 6 h aer injection shows that SrFCl:Nd 2 @PDA NPs is a suitable PA imaging diagnostic agent.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…The rapid in vivo clearance was most likely facilitated by the degradation of SrFCl:Nd 2 in the aqueous environment. Compared to our previous studies where particle clearance from the tumor site was typically observed between 2 to 3 days using much smaller uoride nanocrystals, 5,6,19 the much faster clearance of the much larger SrFCl:Nd 2 @PDA within 12 h post injection suggests that the solubilization of SrFCl was instrumental towards the rapid inorganic nanocrystal clearance. The strong PA signal aer intravenous injection coupled with complete clearance at 6 h aer injection shows that SrFCl:Nd 2 @PDA NPs is a suitable PA imaging diagnostic agent.…”
Section: Resultscontrasting
confidence: 80%
“…Inorganic nanoparticles are widely investigated for therapeutic and diagnostic purposes in both preclinical and clinical phases as they offer numerous unique size-dependent physicochemical, magnetic (e.g., superparamagnetic contrast agents) and optical properties (e.g., quantum dots). [1][2][3][4][5][6] However, there are few instances where inorganic nanomaterials have been used in clinical applications. Unlike their organic or polymeric counterparts, the poor solubility of inorganic crystalline nanomaterials precludes their efficient clearance from the body.…”
Section: Introductionmentioning
confidence: 99%
“…The photothermal (PT) effect has been investigated for biomedical applications in the past two decades, such as the studies on sensing, imaging, therapies, and drug deliveries. 5,6 The PT effect includes two stages, the photonic energy absorption, and photon-induced heat generation. The first stage usually happens in the way of absorption and may exist in other photonic extinction due to the microstructure of the material, such as multiple scattering.…”
Section: Photothermal Effects and Heating Experiments Under Simulatedmentioning
confidence: 99%
“…While the paper discusses the 22 specs for a model HSP, there is also no case study to discuss how to compile 6 the 22 HSP base case specs from the current authoritative data sources. Readers who want learn how to compile 6 Putting the paper's LCOS algorithm in an Excel Workbook allows the reader (author, banker, engineer) to quickly do sensitivity analysis. For the reader to follow this paper, the reader must download this paper's Excel HSP LCOS Financial Algorithm Workbook from this paper's Additional Material Section 7 at SOLAR 20/20 Conference Proceedings Website: [Link].…”
Section: The Levelized Cost Of Storage (Lcos) Algorithm and Its Excelmentioning
confidence: 99%
See 1 more Smart Citation